Constraints on statistical computations at 10 months of age: the use of phonological features - Gonzalez-Gomez, Nayeli; Nazzi, Thierry (Developmental science, 2015)
Recently, several studies have argued that infants capitalize on the statistical properties of natural languages to acquire the linguistic structure of their native language, but the kinds of constraints which apply to statistical computations remain largely unknown. Here we explored French‐learning infants' perceptual preference for labial‐coronal (LC) words over coronal‐labial words (CL) words (e.g. preferring bat over tab) to determine whether this phonotactic preference is based on the acquisition of the statistical properties of the input based on a single phonological feature (i.e. place of articulation), multiple features (i.e. place and manner of articulation), or individual consonant pairs. Results from four experiments revealed that infants had a labial‐coronal bias for nasal sequences (Experiment 1) and for all plosive sequences (Experiments 2 and 4) but a coronal‐labial bias for all fricative sequences (Experiments 3 and 4), independently of the frequencies of individual consonant pairs. These results establish for the first time that constellations of multiple phonological features, defining broad consonant classes, constrain the early acquisition of phonotactic regularities of the native language. The constraints on statistically based acquisition were explored in four different experiments. The results establish for the first time that constellations of multiple phonological features, defining broad consonant classes, constrain the early acquisition of phonotactic regularities of the native language